Bimbingan Penyuluhan Islam: Menumbuhkan Minat Membaca Al-Qur’an bagi Anak Usia Sekolah (13-18 Tahun) di Lingkungan Bataraguru Kecamatan Wolio Kota Baubau - Ardiansyah, Ardiansyah; Nurmin, Nurmin; Fadhilah, Sinta Rahmatil (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Reducing Interest in Reading the Qur'an and the Solution for School-Age Children in RT 01 RW 08, Bataraguru Village, Wolio District, Baubau City. For reading, especially reading the Qur'an among some school-age children (13-18 years old). This also has an impact on their laziness to learn the Qur'an, especially in reading it. They will find many excuses when ordered to read the Qur'an. Moving on from this problem, the researcher finally focused on the role of Islamic counseling guidance in fostering interest in reading the Koran and its solutions for school-age children in RT 01 RW 08 Bataraguru Village, Wolio District, Baubau City. This study aims to find out what are the factors causing a decrease in interest in reading the Qur'an in school-age children (13-18 years old), then help provide solutions in overcoming the decreased interest in reading the Qur'an for school-age children. This research was carried out through a qualitative approach by conducting direct observations in the neighborhood of RT 01 RW 08, Bataraguru Village, Wolio District, Baubau City. Data were obtained by in-depth interviews, observation, and documentation of local communities who were considered capable of providing data. The results of this study found that the factors causing a decrease in interest in reading the Qur'an were family factors that paid less attention to children's religious education, individual factors with indicators of self-will, and TPA management factors. The Islamic counseling guidance efforts carried out in building motivation to learn the Qur'an are giving motivation to children, education in the habit of reciting the Koran, collaborating with parents and mobilizing the environment so that together they provide good religious education to children through reading the Al-Qur'an. In addition, there is innovation in the Al-Qur'an learning system.